Bitten - Sullivan, Louella (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2015)
My poetry investigates the extraordinary in the everyday, exploring my life as a mother and wife, to find the quiet truths that lie there. Using fresh ways of describing familiar experiences, the poems describe tiny, almost-missed moments and voices that have shaped me. Throughout the collection, I imagine my younger selves commenting on my current self and vice versa. Ultimately, my poems use simple words and clean lines to evoke how I feel (and how I want the reader to feel) in each of the moments they describe.
Keywords: Creative writing (Higher education); South African poetry (English) -- Study and teaching (Higher); South African poerty (English) -- 21st century